Inciting Change in Secondary English Language Programs - Coles-Ritchie, M. author. aut Link
XVI, 195 p.
Keywords: This book follows a group of teachers who worked to create a program that supported their students' native languages and funds of knowledge, finding that structures within the school and discourses from other teachers, administrators, and the nation/community both constrained/enabled the teachers to create an equitable learning environment.